Kajian Industri Logam Mendorong Bangkit Adanya Pandemik Covid 19 Di Desa Ngingas Kecamatan Waru Kabupaten Sidoarjo - Andini Nurwulandari; Sugito Efendi; Qoyum Nur Safitri (Multidisiplin Pengabdian Kepada Masyarakat, 2022)
The need for additional production factors in the metal industry can be in the form of physical additions or additional costs; namely, the production value of each factor is the same as the price. Efforts to increase the optimization and efficiency of the use of factors will consequently increase the costs incurred. Therefore, the role of the government in setting prices needs to be done, namely by reducing factor costs or increasing production prices. Likewise, efforts to increase the production of metal goods can be through increasing the optimization of the allocation of production factors by providing information to entrepreneurs, especially information about technology in the use of machine production factors. The role of the government to further increase knowledge for Field Extension Officers (PPL) needs to be further enhanced.